Anti-TLR4 biological response to titanium nitride-coated dental implants: anti-inflammatory response and extracellular matrix synthesis - Oliva, Stefano; Diomede, Francesca; Della Rocca, Ylenia; Mazzone, Antonella; Marconi, Guya Diletta; Pizzicannella, Jacopo; Trubiani, Oriana; Murmura, Giovanna (Frontiers in Bioengineering and Biotechnology, 2023)
Osteointegration is a key process during dental implant placement and is related to titanium surface topography. Implant coating and surface modification methods ameliorate the bone production and the osteogenic process. The current work aimed at evaluating the biological outcomes of two different surfaces of dental implants, machined and titanium nitride (TiN) coated, at an inflammation level using an in vitro model of human periodontal ligament stem cells. The TLR4/MyD88/NF-κB p65/NLRP3 pathway induced by the Porphyromonas gingivalis lipopolysaccharide was studied by means of gene- and protein-level expression. Moreover, the expression of vimentin, vinculin, and fibronectin was evaluated to investigate their effects on the cell adhesion and extracellular matrix deposition. The results of the present study suggest that TiN-coated titanium disks may modulate inflammation by the suppression of the TLR4/MyD88/NF-κB p65/NLRP3 pathway and accelerate extracellular matrix apposition.